New Approaches to the Estimation of the Auditor Organization Activity Quality - Nadirovna, Amerslanova Aynara; Viktorovna, Melnik Margarita (Journal of Reviews on Global Economics, 2018)
The audit activity quality control established in Russia is analyzed. The principal directions in methodology and methods improvement in external and internal quality control considering the audit boundaries expansion, change of targets, which have to be solved in auditor's report, of recent trends in audit service structure, are outlined. On the base of the principal propositions made according to audit examination performed on different levels suggestions for correcting standard and methodic documents regulating the audit activity are substantiated.